Decoding the chromosome-scale genome of the nutrient-rich Agaricus subrufescens: a resource for fungal biology and biotechnology - de Abreu, Carlos Godinho (2023)
Agaricus subrufescens, also known as the “sun mushroom,” has significant nutritional and medicinal value. However, its short shelf life due to the browning process results in post-harvest losses unless it's quickly dehydrated. This restricts its availability to consumers in the form of capsules. A genome sequence of A. subrufescens may lead to new cultivation alternatives or the application of gene editing strategies to delay the browning process. We assembled a chromosome-scale genome using a hybrid approach combining Illumina and Nanopore sequencing. The genome was assembled into 13 chromosomes and 31 unplaced scaffolds, totaling 44.5 Mb with 96.5% completeness and 47.24% GC content. 14,332 protein-coding genes were identified, with 64.6% of the genome covered by genes and 23.41% transposable elements. The mitogenome was circularized and encoded fourteen typical mitochondrial genes. Four polyphenol oxidase (PPO) genes and the Mating-type locus were identified. Phylogenomic analysis supports the placement of A. subrufescens in the Agaricomycetes clade. This is the first available genome sequence of a strain of the “sun mushroom.” Results are available through a Genome Browser (https://plantgenomics.ncc.unesp.br/gen.php?id=Asub) and can support further fungal biological and genomic studies.